Bones Characterisation with Ultrasound - Litniewski, J.; Nowicki, A.; Sawicki, A. (Engineering Transactions, 2001)
Macroscopic, X-ray methods for bone quality assessment are mainly based on porous bone density measurements. The bone quality is a property that is difficult to define, as it is related to both density and structure of the bone. In recent years, several new ultrasonic diagnostic methods have been developed to examine bones "in vivo". These methods are based on measurements of the velocity (SOS – speed of sound) and attenuation (BUA - broadband ulrasound attenuation) of waves penetrating porous bones. The large interest in these methods is a result of the fact that they provide information not only about the bone density but also about their structure without using ionizing energy. The principal element that determines the bone strength is the trabecular structure of a porous bone. In our project we measure acoustic properties of a single trabecula using a scanning acoustic microscope and we introduce the system for "in vivo" measurement of an overall properties of a calcaneus (a heel bone).